Philosophical and Theological Perspectives on the Figure of Job : The Disruptive Challenges of God - Bravo, Nassim,; Charpenel, Eduardo,; López-Farjeat, Luis Xavier, (Philosophy of History and Culture ;, 2026)
The Book of Job remains one of the most profound and unsettling texts in religious and philosophical thought, raising timeless questions about suffering, justice, and the human relationship with the divine. Philosophical and Theological Perspectives on the Figure of Job brings together a diverse collection of essays that explore Job's narrative from multiple perspectives-philosophical, theological, comparative, and literary-without reducing its complexity or imposing a singular interpretation. Engaging with thinkers such as Kant, Kierkegaard, and René Girard, as well as Islamic kalām , William Blake's visual reinterpretations, and María Zambrano's poetic reason, this volume examines Job both as a subject of inquiry and as a figure that continues to challenge and inspire. Rather than offering definitive answers, these essays preserve the tensions within Job's story, demonstrating its enduring relevance in contemporary debates on suffering, justice, and the limits of human understanding.